Cable-Driven Parallel Robots - Bruckmann, Tobias; Pott, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This publication presents the outcome of the "First International Conference on Cable-Driven Parallel Robots" in 2012. This is the first conference to bring together the cable robot community and dedicate a forum for the international experts of this field. It contains the Know-how, ideas and experiences of active researchers developing cable-driven robots. The book presents the state of the art, including summarizing contributions and latest research results and, where relevant, the future outlook. The book covers the essential topics for cable-driven robots: classification and definition, kinematics, workspace analysis, cable modeling, control and calibration, design methodology, hardware/prototype development, experimental evaluation, application reports and new application concepts.
Welcome -- Motion Planning -- Force Distribution -- Application and Protoypes -- Design and Components -- Kinematics and Interval Methods -- Calibration und Identification -- Control -- Dynamics Modelling.
Keywords: Engineering; Engineering design; Engineering; Robotics and Automation; Engineering Design